Tactile and interpersonal sound symbolic associations in patients with multiple somatic symptoms - Yi Li; Xiquan Ma; Xiaoming Jiang; Qiang Feng; Lu Wang (Scientific Reports)
Abstract Patients with functional somatic symptoms (FSS) have distorted exteroception and interoception. It is unclear whether they also process and associate sounds and tactile/interpersonal factors differently. This study investigates the differences in how patients with multiple somatic symptoms (SS-high) and those without functional somatic disorders (SS-low) associate features of Mandarin rimes with tactile and interpersonal properties. Two groups of participants listened to rime chains consisting of two identical Mandarin rimes. They rated sound stimuli on five-point scales for smooth-rough, light-heavy, polite-rude, and friendly-hostile. Linear mixed-effects models and representational similarity analyses showed that both groups relied on duration and F0 for all four dimensions, and on alveolar nasal rimes and ΔF1 for the smooth-rough dimension. Beyond commonalities, the study also found that the two groups of participants weighed F1–F3 and nasality differently when associating rimes with tactile and interpersonal dimensions. Mediation analyses revealed differing mechanisms for sound symbolism between the groups. In the SS-high group, the smooth-rough dimension mediated the association between duration and the polite-rude dimension, which aligned with the Transitivity Proposal. In the SS-low group, the relationship between duration and smoothness was mediated by politeness, supporting the Emotion Mediation Hypothesis. This study highlights the importance of considering both tactile and interpersonal dimensions in sound symbolism research, especially in clinical populations with FSS.